Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1108/08876040110381328
|View full text |Cite
|
Sign up to set email alerts
|

How much more are consumers willing to pay for a higher level of service? A preliminary survey

Abstract: A survey was conducted using conjoint analysis to determine how consumers perceived the relative importance of price vs. quality of service in the selection of restaurants. The use of conjoint analysis enables one to mimic the trade‐off situation in a consumer’s choice process. The results showed that price was a more important factor than quality of service. Estimates are also made regarding how much more respondents are willing to pay for a higher level of service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 19 publications
3
56
2
2
Order By: Relevance
“…Price premiums, the excess prices paid over and above the "fair" price that is justified by the "true" value of the product, may be indicators of consumers' demand for that product (Tse, 2001). WTP for Eco-labelled food products can be a good predictor of these food products demand.…”
Section: Willingness To Pay For Minimally Processed Vegetable Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Price premiums, the excess prices paid over and above the "fair" price that is justified by the "true" value of the product, may be indicators of consumers' demand for that product (Tse, 2001). WTP for Eco-labelled food products can be a good predictor of these food products demand.…”
Section: Willingness To Pay For Minimally Processed Vegetable Productsmentioning
confidence: 99%
“…A large body of research regarding consumers' willingness to pay (WTP) for environmental friendliness and/or quality/safety in food production (Ballestrazzi et al, 2011;Husted, Russo, Meza, & Tilleman, 2014;Nassivera & Sillani, 2015;Rosa & Nassivera, 2013), as well as for non-food products (Laroche, Bergeron, & Barbaro-Forleo, 2001;Sexton & Sexton, 2014;Vlosky, Ozanna, & Fontenot, 1999) or services (Johnston, Schultz, Segerson, Besedin, & Ramachandran, 2013;Tse, 2001) can be found. Price premiums, the excess prices paid over and above the "fair" price that is justified by the "true" value of the product, may be indicators of consumers' demand for that product (Tse, 2001).…”
Section: Willingness To Pay For Minimally Processed Vegetable Productsmentioning
confidence: 99%
“…Tse (2001), for example, empirically demonstrated that service quality affects the consumer selection process. Zeithaml (1991) made the same argument from a conceptual perspective.…”
Section: Quality Of the Servicementioning
confidence: 99%
“…So, if the consumer perceives that organic food has value (e.g. egocentric values, such as health or pleasure) (Zanoli & Naspetti, 2002) and benefits, they might be willing to pay a higher price (Tse, 2001;Shaharudin et al, 2010). Organic food purchases are largely connected to consumers' environmental concerns, concerns about food quality, and/or safety.…”
Section: A Marketing MIXmentioning
confidence: 99%